2017
DOI: 10.1111/jftr.12228
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Meta‐Analyses of Research on Interpersonal Acceptance–rejection Theory: Constructs and Measures

Abstract: This article is an overview of 12 meta‐analyses conducted to test the basic postulates of interpersonal acceptance–rejection theory (IPARTheory). These meta‐analyses are based on a total of 551 (48% unpublished and 52% published) studies on the theory. The studies were conducted over period of 42 years, from 1975 through 2016. They represent an aggregate sample of 149,440 respondents, including males and females, children and adults. Respondents were taken from 31 countries on five continents. The findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
3
28
0
1
Order By: Relevance
“…However, other studies have suggested that parental acceptance is a more relevant factor for boys than for girls, and even that father´s rejection is the most influential in boys and girls [ 31 ]. Finally, we can observe how our results complement the international studies on parental acceptance-rejection [ 80 ], providing a greater influence of the rejection of fathers and mothers in children of the opposite sex, between 11 and 14 years old.…”
Section: Discussionsupporting
confidence: 76%
“…However, other studies have suggested that parental acceptance is a more relevant factor for boys than for girls, and even that father´s rejection is the most influential in boys and girls [ 31 ]. Finally, we can observe how our results complement the international studies on parental acceptance-rejection [ 80 ], providing a greater influence of the rejection of fathers and mothers in children of the opposite sex, between 11 and 14 years old.…”
Section: Discussionsupporting
confidence: 76%
“…The responsiveness dimension, also termed warmth, affect, or acceptance [14], has generated a large volume of research attesting to its importance in offspring’s positive development, flourishing, and emotional development (e.g., self-esteem, subjective well-being, lower risk of behavioral problems, mood disorders [13,15,16,17], or drug consumption [18]). This relation with positive adjustment has been observed all the way to adulthood across many different cultures [19,20].…”
Section: Introductionmentioning
confidence: 70%
“…Nevertheless, in line with that reported by previous research [17], the findings of the present study also highlight the importance of the father figure in the establishment of family style, which is why it is important to involve men more in children’s upbringing and care, as well as in parenting support programs and interventions [94]. Given that children’s upbringing is influenced by both the presence and absence of certain elements, and in light of the importance of affect and communication for both the establishment of family style or climate and adolescent development and adjustment [14,15,19,20], it is vital to develop programs and actions which seek to foster and promote the knowledge and use of positive parenting practices based on communication, affect, and listening. It is also imperative to implement policies designed to disseminate the importance of fathers’ involvement in their children’s upbringing, not only during childhood but also during adolescence, a developmental stage that is especially complex [5] due to the number of challenges young people must face at the same time, and during which, despite the growing importance of peers and friends, family continues to play a key role.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies included multiple markers of adjustment problems (e.g., Cummings et al, ; Juang et al, ), whereas other studies focused on both adjustment problems and positive well‐being (e.g., Fosco & Lydon‐Staley, ; Leeman et al, ). Khaleque and Ali () conducted a review of several meta‐analyses conducted across 31 countries, for example, and found robust support for moderate‐sized associations between parental acceptance and a variety of youth outcomes such as a more positive worldview and fewer socioemotional problems. In individual studies of families with young adolescents, maternal support was associated with youth prosocial behaviors toward family members, whereas paternal support was associated with youth prosocial behaviors with friends (Padilla‐Walker, Nielson, & Day, ).…”
Section: Complexity and Specificitymentioning
confidence: 99%